When parenting does not 'come naturally': providers' perspectives on parenting education for incarcerated mothers and fathers. Issue 1 (2nd January 2018) - Fowler, Cathrine; Dawson, Angela; Rossiter, Chris; Jackson, Debra; Power, Tamara; Roche, Michael
ABSTRACT: Learning to parent sensitively and safely can be challenging for adults with childhood abuse and neglect experiences. Such childhood experiences are prevalent among incarcerated parents whose ability to parent their own children is also limited by separation from them. Several prisons have developed programs to foster pro-social parenting skills among incarcerated mothers and fathers to assist them on release. This paper reports a qualitative research study that explored the factors affecting the delivery and outcomes of parenting programs in correctional facilities in New South Wales Australia from the perspective of individuals involved in developing and implementing the programs. Thematic analysis of 19 interviews identified two main themes: supporting parents' learning in correctional settings and providers' learning about parent education in correctional settings. Respondents reported the benefits of providing creative learning opportunities enabling parents to build on their strengths and to develop relationships. These factors contributed to changing prisoners' attitudes and supporting them to consider alternative parenting approaches. The co-productive approach to parent education supported enhanced parenting knowledge among parents and greater insights among educators. Parenting education can be successfully delivered in correctional settings and can assist incarcerated parents to build on existing knowledge and adapt it to their own needs.